The performance of Islamic and conventional banks during and after the global financial crisis / Zulaiha Abdullah - Abdullah, Zulaiha (2014)
The research investigates the performance of Islamic and Conventional Banks during and after the global financial crisis from the period of 2008 to 2011. Data were collected from five Islamic Banks and five Conventional Banks based on their asset size from the period of 2008 to 2011 for the during and after the global financial crisis. During the global financial crisis, it is include from the year 2008-2009 and for the 2010-2011 is for the after global financial crisis. The financial ratio such as Net Income (Nl), Return on Asset (ROA), and Return on Equity (ROE), Total Asset (TA) and Net Interest Margin (NIM) are used to assess the banking performance. The method used to analyze the data of this study is Pooled Ordinary Least Square (POLS) Regression analysis. The reasons use the Pooled Ordinary Least Square (POLS) Regression because this study conducted between the multiple years and multiple of banks. This study was using the panel data approach.